Peranan Reserse Kriminal dalam Mengungkap Tindak Pidana Pencurian Kendaraan Bermotor di Wilayah Hukum Polsek Ubud - I Gusti Ngurah Arya Brahmantara; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati (Warmadewa Press, 2020)
The rise of crimes occurred in almost all over the world has appeared as the limelight not only for the security forces and the community but also for scholars or researchers to strive for uncovering the motives beyond the criminal acts and the strategies for prevention and settlement. As is the case in Indonesia, especially in the Bali territory - the main center of Indonesian tourism activities - crimes in various forms have often taken place. This study reveals the police efforts in uncovering the criminal acts of motor vehicle theft occurred at Jalan Andong, Desa Petulu, Ubud - Bali, as well as the inhibiting factors encountered. The study makes use of qualitative research design and empirical and sociological legal research methods. The results showed that there were two actions the police had taken. First, pre-emptive action was realised through community guidance through Non-Commissioned Officer (NCO) for People’s Security and Order (most commonly known as BHABINKAMTIBMAS in Indonesia). The second is preventive action through patrol activities and control of the completeness of motorised vehicles. The latter is a repressive measure, in which the police took actions according to the police report models (A) and (B). In an effort to disclose this action, several obstacles were encountered, including: internal factors appearing in the form of inadequate number of investigators, facilities and equipment such as fingerprint scanners which were also inadequate and a limited budget; and external factors which include inadequate CCTV, the minimum number of witnesses, negligence of vehicle owners, perpetrators and stolen property had been outside Bali. The lack of witnesses, especially but not limited to recidivists, in an effort to expose the crime implies that sophisticated and adequate facilities and equipment have the crucial functions, benefits, and urgency to be equipped in order to realise national security and peace. Related to this, Criminal Investigation Agency holds a crucial role that needs to be realised immediately.